In-situ synthesis of NiO foamed sheets on Ni foam as efficient cathode of battery-type supercapacitor. (10th April 2018) - Fan, Yuqian; Ma, Zhipeng; Wang, Lumeng; Dong, Yue; Jiang, Tianhang; Li, Zixuan; Liu, Liang; Shao, Guangjie
Abstract: Herein we report an in-situ strategy for synthesizing NiO foamed sheet on Ni foam substrate which could achieve great improvement on the areal performance of battery-type supercapacitors. The anchored NiO foamed sheets are synthesized via a precursor growth step by hydrothermal oxidation, and followed by a pore-inducing step through heat treating. The physical characterizations indicate that this film product has a multi-level pore structure with high active surface area. As for electrode material, the anchored sheets could ensure excellent conductivity at the film/substrate interface, and the porous structure could form high free electron/ionic diffusion routes which facilitates the redox reactions for reversible energy storage. The electrochemical measurements show that the areal capacity of as-synthesized electrode could achieve 4.31–3.39 C cm −2 at a wide current range of 10–200 mA cm −2 . The single supercapacitor device exhibits a high areal energy density of 9.84–9.45 W h m −2 at a wide power density of 100–2000 W m −2 .